A Comparative Study on MHD Forced Convective Flow of Different Nanofluids with Water (H2O) as Base Fluid in a Vertical Rectangular Duct - Bishnu Ram Das; P.N. Deka (East European Journal of Physics, 2024)
In this paper, a comparative study on MHD forced convective flow for heat transfer efficiency of different nanofluids with water (H2O) as base fluid has been carried out. Here, in this study flow through vertical rectangular has been considered in presence of strong magnetic field. In this laminar flow we consider duct walls as electrically non-conducting where the transverse magnetic field acting normally on the duct walls. Joule heat and the viscous dissipation effects are included in the energy equation and furthermore the walls of the duct are kept at constant temperature. An explicit finite difference method has been adopted with fine grid in the control volume for solving the governing equations of this MHD nanofluid flow. Computational processes are carried out using MATLAB code. In this present work we have plotted the flow fields velocity, induced magnetic field, and temperature for various values of MHD flow parameters graphically by varing thermal Grashof number (Gr), Hartmann number (Ha), Reynold number (Re), Eckert number (Ec), Prandtl number (Pr), magnetic Reynold number (Rm), and nanoparticle volume fraction (ϕ)  respectively.